Amidas derivadas do ácido vanílico: reações de acoplamento e bioatividade - Oliveira, Ana Júlia de Morais Santos (2018)
In the last decade a considerable increase in the prevalence of resistance to antimicrobial agents was observed, which motivated the study of the present work, whose purpose was the preparation of a collection of amides derived from vanillic acid through coupling reactions using PyBOP (benzotriazol-1-yloxytripyrrolidinophosphonium hexafluorophosphate) and DCC (dicyclohexylcarbodiimide) as coupling agents, as well as to evaluate the antimicrobial activity of amides prepared against species of the genus Candida, Staphylococcus and Pseudomonas. In this context, there are the phenolic compounds, which can be extracted from natural sources or obtained by means of synthesis, for example, vanillic acid that has several biological activities, such as antimicrobial. In the characterization of the amides were used Infrared Spectroscopic Methods, 1H and 13C Nuclear Magnetic Resonance and High Resolution Mass Spectrometry. All the amides were submitted to antimicrobial tests by the broth microdilution method, with antimicrobial control as nystatin and caspofugin. The ten amides were obtained with yields varying between 28,81 - 86,44%, and three are unpublished. All the amides presented antifungal activity in at least one strain tested. In the antibacterial evaluation, all the amides presented bioactivity in the highest concentration tested against Staphylococcus aureus strain ATCC 25925. The amide with the best antifungal profile was AN05 which had a minimum inhibitory MIC concentration of 0,46 μmol / mL , suggesting that the presence of a methyl group bound to the aromatic ring potentiates the activity of the molecule. The presence of hydroxyl groups in the ortho and para positions, and the presence of methoxyl in the meta position are also important for antimicrobial activity.